EXTRACELLULAR MODULATORY AND ANTI-INFLAMMATORY EFFECTS OF A COMBIATION OF CURCUMIN, PIPERINE, AND VIRGIN COCONUT OIL IN ANIMAL MODEL - ADITYA ASISH; SONY RAJAN; SVENIYA P JOSE; SHEETHAL S; RATHEESH M; SANDYA S (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The current study investigated the potential of a novel herbal combination of curcumin, piperine, and virgin coconut oil to exhibit anti-inflammatory and anti-rheumatic properties against carrageenan-induced inflammation. Method: A minimal dose of the drug formulation having a maximal anti-inflammatory effect was found (Dose III). Following the completion of the experiment, the animals were humanely euthanized, and paw tissue and serum samples were collected for further analysis. The expression levels of mRNA for Tumor Necrosis Factor-alpha (TNF-α), interleukin (IL)-6, PGE-2, and Thiobarbituric acid reactive substance (TBARS), as activities of cyclooxygenase -2, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and TBARS were measured and levels of matrix metalloproteinases (MMP)9 and MMP2 were measured using zymography and western-blotting. Results: Anti-oxidant assays were performed in serum and synovial tissue, observed that the production of anti-oxidant enzymes such as SOD, GPx, CAT, and GSH was enhanced, and suppression of the accumulation of lipid peroxidation products in the group treated with the potent dose of the drug combination. A decrease in the mRNA expression of IL-6, IL-1β, and TNF α was noted in the treatment group, these are the upstream events of the inflammatory cascade. Radiological and histopathological analysis confirms that the drug formulation acted on MMPs to reduce its baneful consequence. Conclusion: The drug formulation’s anti-inflammatory and anti-rheumatic properties, combined with its multi-targeted mechanism, suggest its potential as a therapeutic agent for various inflammatory diseases.